Juridical Analysis of Indonesian Parliamentary Ethical Committee: Analyzing Supervision Function within Indonesian Parliament - Widodo, Wahyu; Galang Windi Pratama, Toebagus; Orwela, Citra (International Journal of Law Reconstruction, 2024)
This research was made under the basis that the role of the People's Representative Council (Dewan Perwakilan Rakyat/DPR) the Republic of Indonesia supervision that fell to the Parliamentary Ethical Committee (Mahkamah Kehormatan Dewan/MKD) has not yet been fair and how to ensure that the Ethical Implementation in Indonesian Parliament can be done properly in a constructivism paradigm where the type of research method used is normative juridical and the specifications of this research have a descriptive-analytical nature with the approach used by the author being a statutory approach. The research results found that the supervision by the DPR of the Republic of Indonesia Honorary Court has not yet been fair was because most of Ethical Committee Member were fellow DPR Member causing the political interests of the respective political parties does not want their members to be sanctioned, even at the cost of not upholding the DPR ethics. Therefore, to improve the system for handling cases and supervision, the DPR Honorary Body, researchers found several solutions that can be implemented based on comparisons with Ethics Committees in the Parliaments of other countries. First, strengthening the independence of the Ethical Committee through external, non-partisan selection processes would mitigate political influence. Clearer ethical codes with enforceable penalties are crucial, ensuring accountability for violations. Legal protections to shield Ethical Committee decisions from political pressures are also proposed. Expanding Ethical Committee authority and sanctions, alongside mandatory public reporting, would enhance transparency and compliance. These reforms aim to address current challenges and elevate ethical standards within the Indonesian Parliament effectively.